Guide de base pour l'evaluation du bien-etre social the BAG - Colfer, C.J.P.; Brocklesby, M.A.; Diaw, C.; Etuge, P.; Günter, M.; Harwell, E.; McDougall, C.; Porro, N.M.; Porro, R.; Prabhu, Ravi; Salim, A.; Sardjono, M.A.; et al. (Center for International Forestry Research, 2000)
The BAG focuses on the social criteria and indicators for sustainable forest management, a topic that has been the subject of considerable controversy and uncertainty. It is designed for people interested in assessing sustainable forest management, but who do not have a high degree of expertise in social sciences. This manual describes six simple methods designed for use by biophysical scientists with a college education. These methods can also be used by assessors with higher levels of expertise in social sciences, but they are presented in a 'cookbook' format. 'The Scoring and Analysis Guide', to be used with 'the BAG', provides additional help in making assessments of human well being, including a specific scoring method. It also provides increasingly detailed levels of guidance in analysis.